Finite extinction for a doubly nonlinear parabolic equation of fast diffusion type - Md Abu Hanif Sarkar (Arab Journal of Mathematical Sciences, 2022)
Purpose – The purpose of this paper is to find a doubly nonlinear parabolic equation of fast diffusion in a bounded domain. Design/methodology/approach – For positive and bounded initial data, the authors study the initial zero-boundary value problem. Findings – The findings of this study showed the complete extinction of a continuous weak solution at a finite time. Originality/value – The extinction time is studied earlier but for the Laplacian case. The authors presented the finite extinction time for the case of p-Laplacian.